Analisis Faktor Penyebab Rendahnya Keterampilan Menulis Belajar Siswa SD Kelas IV - Laila Qadaria; Khoirul Bariah Rambe; Wapiatul Khairiah; Rahmanita Minta Ito Pulungan; Elvira Zahratunnisa (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to analyze the causes of writing skills. Grade IV elementary school students involved in this research. In this case the author uses the library research method, which is research conducted by analyzing and making written literature in scientific journals as well as the main source. Writing difficulties are also known as dysgraphia. One of the internal factors that causes students to have difficulty writing is weak fine motor skills, weak visual memory skills, low interest and motivation to learn. And external factors that cause students to have difficulty writing, namely: lack of attention from parents to students, unsupportive home atmosphere, strategies for dealing with writing difficulties through participatory learning in schools that are used by teachers, namely first to provide motivation to students. Second, use interesting learning media in learning to write.